KINERJA ALAT PENGERING KUNYIT BERSUMBER PANAS HAIR DRYER - Agung Samudra; Fachri Rofi (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2023)
Turmeric is a plant that is included in the spice plant category and is also a family medicinal plant (TOGA) which is good for health. However, in the drying process they still use the traditional method of drying in the sun, so this method is less effective because it has to depend on the weather. Therefore there must be a new innovation, namely using a dryer. In this study, the dryer used was an oven that had been designed using a hair dryer as the heat source. The purpose of this study was to determine the performance of the turmeric dryer with a hair dryer as a heat source. This type of research is a pure experimental research. The research object is an oven-shaped dryer that uses a hair dryer as a heat source. After conducting performance tests, the turmeric dryer can work well. This study uses 3 time variants, namely, 30, 60, and 90 minutes. Testing at 55°C was the most efficient time, namely 90 minutes with an initial weight of 200 grams to 118 grams which experienced higher shrinkage than 30 minutes and 60 minutes. The longer the drying time, the better the drying results.